2023
DOI: 10.3389/fimmu.2023.1123600
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HSPA14 in patients with acute HIV-1 infection and its effect on HIV-1 replication

Abstract: IntroductionHeat shock protein (HSPs) are important intracellular factors, which are often involved in the regulation of viral replication including HIV-1 in infected individuals as molecular chaperone proteins. Heat shock proteins 70 (HSP70/HSPA) family play important roles in HIV replication, but this family contain many subtypes, and it is unclear how these subtypes participate in and affect HIV replication.MethodsTo detect the interaction between HSPA14 and HspBP1 by CO-IP. Simulating HIV infection status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Although extensive HIV research has identified viral-host protein interactions that disrupt autophagy [52,53], recent studies further demonstrate dysregulation in other proteostasis mechanisms. The expression of many molecular chaperones, particularly heat shock proteins, are altered with high viremia during acute HIV [54] and auxiliary HIV protein Nef can modulate the ubiquination of various cellular proteins, either increasing their stability or promoting degradation [55,56].…”
Section: Biological Aging Hallmarksmentioning
confidence: 99%
“…Although extensive HIV research has identified viral-host protein interactions that disrupt autophagy [52,53], recent studies further demonstrate dysregulation in other proteostasis mechanisms. The expression of many molecular chaperones, particularly heat shock proteins, are altered with high viremia during acute HIV [54] and auxiliary HIV protein Nef can modulate the ubiquination of various cellular proteins, either increasing their stability or promoting degradation [55,56].…”
Section: Biological Aging Hallmarksmentioning
confidence: 99%